Performance on the Defense Automated Neurobehavioral Assessment across controlled environmental conditions. Issue 6 (1st November 2016) - Haran, F. Jay; Dretsch, Michael N.; Bleiberg, Joseph
ABSTRACT: Neurocognitive assessment tools (NCAT) are commonly used to screen for changes in cognitive functioning following a mild traumatic brain injury and to assist with a return to duty decision. As such, it is critical to determine if performance on the Defense Automated Neurobehavioral Assessment (DANA) is adversely affected by operationally-relevant field environments. Differences in DANA performance between a thermoneutral environment and three simulated operationally-relevant field environments across the thermal stress continuum were calculated for 16 healthy U.S. Navy service members. Practice effects associated with brief test-retest intervals were calculated within each environmental condition. There were no significant differences between the simulated environmental conditions suggesting that performance on the DANA Brief is not impacted by thermal stress. Additionally, there were no significant differences in performance within each simulated environmental condition associated with repeated administrations.